2023
DOI: 10.3390/mi14020294
|View full text |Cite
|
Sign up to set email alerts
|

Direct Processing of PVD Hard Coatings via Focused Ion Beam Milling for Microinjection Molding

Abstract: Hard coatings can be applied onto microstructured molds to influence wear, form filling and demolding behaviors in microinjection molding. As an alternative to this conventional manufacturing procedure, “direct processing” of physical-vapor-deposited (PVD) hard coatings was investigated in this study, by fabricating submicron features directly into the coatings for a subsequent replication via molding. Different diamondlike carbon (DLC) and chromium nitride (CrN) PVD coatings were investigated regarding their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Research on the microforming process is developing at a very intensive pace, leading to the gradual elimination of the limitations of this process. In the process of injection microforming, thermoplastic materials are mostly used, and thermosetting materials are used to a lesser extent [157,158]. However, it should be mentioned that when thermoplastics are used, mostly those with low viscosity are used.…”
Section: Microinjection Moldingmentioning
confidence: 99%
“…Research on the microforming process is developing at a very intensive pace, leading to the gradual elimination of the limitations of this process. In the process of injection microforming, thermoplastic materials are mostly used, and thermosetting materials are used to a lesser extent [157,158]. However, it should be mentioned that when thermoplastics are used, mostly those with low viscosity are used.…”
Section: Microinjection Moldingmentioning
confidence: 99%
“…Orth et al 18 found that the use of coated steel molds resulted in higher molding efficiency and 20% ~ 30% improvement in replication quality. Ruehl et al 19 successfully replicated submicron structures with an aspect ratio of 0.4:1 (height 190 nm) by using injection compression molding and found that the fidelity of replicating submicron structures and the demolding behavior depended on the combination of coatings and polymers. Zhang et al 20 demonstrated that the nickel‐based composite molds fabricated by electroforming could effectively reduce the friction coefficient and improved the polymer microstructure quality during hot embossing.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the process can be integrated into existing microfabrication workflows like hot embossing, enabling scalability for mass production. [69,70] This study focuses on the surface modifications of thermoplastic COC polymers, specifically the TOPAS brand, for achieving selective cell adhesion using middle-energy ion beam patterning. We explored the use of energetic ions of oxygen, nitrogen, and carbon with fluences of 3.75 × 10 12 , 3.75 × 10 13 , and 3.75 × 10 14 cm −2 at an energy of 600 keV.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the process can be integrated into existing microfabrication workflows like hot embossing, enabling scalability for mass production. [ 69,70 ]…”
Section: Introductionmentioning
confidence: 99%